Allegations of child sexual abuse in parenting disputes: An examination of judicial determinations in the Family Court of Australia. Issue 2 (3rd April 2018) - Ferguson, Claire; Wright, Sarah; Death, Jodi; Burgess, Kylie; Malouff, John
ABSTRACT: This study examined Family Court of Australia (FCA) judicial determinations in parenting disputes when allegations of child sexual abuse (CSA) are made by an interested party, usually the mother. For the study, 156 published judgments from 2013–2015 were examined to measure how often allegations of CSA are substantiated, suspected to be true, and disbelieved. The characteristics most common in substantiated versus unsubstantiated cases, evidence of abuse presented, and resulting parenting orders were assessed. Findings indicate that, against international comparisons, FCA judges substantiate cases very conservatively, with rates of substantiation much lower than in other studies. Allegations made by mothers against fathers were disproportionately unsubstantiated, as were those which did not fall under the Magellan case management system. Cases where the only evidence of CSA was a child's disclosure and parent's allegation were common in both substantiated and unsubstantiated cases, meaning that a lack of other evidence does not preclude a positive finding of risk of CSA by the FCA. Those cases also involving a protection order against the accused were more likely to be substantiated. Confirmation biases and a judicial tendency to err on the side of false negatives are discussed.